2021
DOI: 10.1038/s41390-021-01731-z
|View full text |Cite|
|
Sign up to set email alerts
|

Electrocardiogram for heart rate evaluation during preterm resuscitation at birth: a randomized trial

Abstract: Background Although electrocardiogram (ECG) can detect heart rate (HR) faster compared to pulse oximetry, it remains unknown if routine use of ECG for delivery room (DR) resuscitation reduces the time to stabilization in preterm infants. Methods Neonates <31 weeks’ gestation were randomized to either an ECG-displayed or an ECG-blinded HR assessment in the DR. HR, oxygen saturation, resuscitation interventions, and clinical outcomes were compared. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It may take up to a minute to have reliable pulse oximetry readings for HR and SpO 2 . Heart rate can be rapidly counted by auscultation, which is not as accurate as oximetry or ECG [57]; however, it is not clear whether rapid ECG-derived HR signal confers any meaningful clinical benefit [58]. Caregivers are quite capable of determin-ing when HR <60 or above 100 bpm which is all that is needed [59].…”
Section: Delivery Room Stabilisationmentioning
confidence: 99%
“…It may take up to a minute to have reliable pulse oximetry readings for HR and SpO 2 . Heart rate can be rapidly counted by auscultation, which is not as accurate as oximetry or ECG [57]; however, it is not clear whether rapid ECG-derived HR signal confers any meaningful clinical benefit [58]. Caregivers are quite capable of determin-ing when HR <60 or above 100 bpm which is all that is needed [59].…”
Section: Delivery Room Stabilisationmentioning
confidence: 99%
“…The only exception was a lower proportion of infants intubated in the delivery room in an observational study when electrocardiographic monitoring was used, 219 a result that was not confirmed in the meta-analysis of 2 RCTs. 217,218 The potential advantages of rapid signal acquisition and continuous, accurate heart rate monitoring need to be weighed against the potential costs of equipment and training.…”
Section: Neonatal Life Supportmentioning
confidence: 99%
“…The SysRev identified 2 RCTs 217,218 involving 91 newborn infants and 1 cohort study 219 involving 632 newborn infants.…”
Section: Neonatal Life Supportmentioning
confidence: 99%
“…We identified 120 studies that were entered into Cochrane CENTRAL 2017 to 2021 and met our inclusion criteria (eFigure 1 in Supplement 1). There was a range in the articles’ availability via electronic publication (2016-2021) and publication year (2017-2023).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows that the distribution of reporting vs not reporting race and ethnicity data in NICU clinical studies over the 5 years evaluated. We assessed reporting by NIH funding: of the 52 studies funded by the NIH, 35 studies (67%) included race and ethnicity data. Among 68 studies not funded by the NIH, 40 studies (58%) reported race and ethnicity data; the difference between NIH-funded and non-NIH–funded studies was not statistically significant by Pearson χ 2 .…”
Section: Resultsmentioning
confidence: 99%